Methionine plus Cystine Levels for Light Laying Hens on Production Phase (Research, Society and Development, 2021)
The objective of this study was to evaluate the levels of sulfur amino acids in the diets of laying hens of 34-50 weeks of age. 336 Dekalb White birds were distributed in a completely randomized design with six treatments, 14 replicates of four birds each. The diets consisted in a control treatment, formulated to meet the nutritional requirements of sulfur amino acids according to the NRC (1994) and five diets varying in methionine plus cystine level (0.536, 0.603, 0.670, 0.737, 0.804%). Performance, egg quality and histological data were evaluated. There was a significant quadratic effect for production and egg mass and mass and dozen conversion per eggs, with methionine plus cystine estimations of 0.691%, 0.689%, 0.737% and 0.730%, respectively. Methionine plus cystine levels significantly affected the histology of tissues. The level of 0.737% of digestible methionine plus cystine, with 90% of methionine plus cystine: lysine ratio, and 756.53 mg/bird/day of consumption, is recommended to light laying hens in the production phase.